Dietary supplementation by older adults in southern China: a hospital outpatient clinic study - Lee Andy H; Liang Wenbin; Binns Colin W (BMC, 2009)
Abstract Background There has been little knowledge about dietary supplementation by the Chinese elderly. The aim of this cross-sectional study was to investigate the usage of dietary supplements by older adults in southern China. Methods A total of 600 community-dwelling older adults were recruited from the outpatient clinics of three major hospitals in Foshan city between July 2007 and July 2008. Face-to-face interviews of participants were conducted to obtain information on demographics, lifestyle and dietary supplements use. Frequency and duration of usage were recorded for six categories of dietary supplements. Results Among the 446 consented participants (241 men and 205 women) who were over 55 years of age, 19.1% consumed one or more types of dietary supplements. The prevalence of usage was significantly higher (p = 0.008) for females (24.4%) than for males (14.5%). Dietary supplements were more likely to be consumed by non-smokers (p = 0.021) and those with hyperlipidemia (p = 0.003). The most popular supplement among users was calcium (53%). The majority (71%) of the users consumed supplements on a regular basis at one or more times per day, with an average duration of 2.95 (SD 4.80) years. Conclusion The overall prevalence of dietary supplementation in this older Chinese population was considerably lower than those in other Asia-Pacific countries.